2015
DOI: 10.1590/s0034-8910.2015049005944
|View full text |Cite
|
Sign up to set email alerts
|

Occupational conditions and the risk of the use of amphetamines by truck drivers

Abstract: OBJECTIVE To test whether the occupational conditions of professional truck drivers are associated with amphetamine use after demographic characteristics and ones regarding mental health and drug use are controlled for.METHODS Cross-sectional study, with a non-probabilistic sample of 684 male truck drivers, which was collected in three highways in Sao Paulo between years 2012 and 2013. Demographic and occupational information was collected, as well as data on drug use and mental health (sleep quality, emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 19 publications
0
21
1
17
Order By: Relevance
“…Dessa forma, foram expressivos os métodos de estudo de caso Olsona, Hahnb e Buckerta, 2009;Raffler, et al, 2016;Stevenson et al, 2010), simulação (Bunce et al, 2012;Cantin et al, 2009;Kaber et al, 2012, Makishita & Matsunaga, 2008Nabatilan et al, 2012;Neubauer et al, 2012;Pauzie, 2008) Okunribidoa, Magnussonb & Pope, 2006;Olsona, Hahnb & Buckerta, 2009). Motoristas de caminhão de carga pesada e longa distância (Oliveira, 2015;Knauth et al, 2011;Stevenson et al, 2010).…”
Section: Primeira Lente: Metodologia Aplicadaunclassified
See 1 more Smart Citation
“…Dessa forma, foram expressivos os métodos de estudo de caso Olsona, Hahnb e Buckerta, 2009;Raffler, et al, 2016;Stevenson et al, 2010), simulação (Bunce et al, 2012;Cantin et al, 2009;Kaber et al, 2012, Makishita & Matsunaga, 2008Nabatilan et al, 2012;Neubauer et al, 2012;Pauzie, 2008) Okunribidoa, Magnussonb & Pope, 2006;Olsona, Hahnb & Buckerta, 2009). Motoristas de caminhão de carga pesada e longa distância (Oliveira, 2015;Knauth et al, 2011;Stevenson et al, 2010).…”
Section: Primeira Lente: Metodologia Aplicadaunclassified
“…Dentre outros métodos utilizados em paralelo com a análise da carga de trabalho, destacaram-se: questionário para avaliar o risco de desenvolvimento de dependência, associado ao uso de anfetaminas e outras drogas (ASSIST-WHO, versão 3.1) (Oliveira, 2015), Estresse emocional (Inventário de Sintomas de Estresse para Adultos de Lipp -ISSL)(…”
Section: Conceitos E Contextos Sobre Carga De Trabalhounclassified
“…(1,3) Several authors have conducted studies to identify professions with working conditions that promote alcohol consumption, such as gravediggers, nurses, truckers, street cleaners, and self-employed workers. (3,(4)(5)(6) In addition, socially under-privileged activities, work in dry, hot or polluted locations, and positions that cause mental or physical fatigue leading to burnout have been associated with the use of alcohol as relief for tension and suffering. (3)(4)(5)(6) Some researchers have investigated the sociodemographic factors associated with alcohol use among workers; (7,8) however, studies with the specific population of maintenance workers were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…(3,(4)(5)(6) In addition, socially under-privileged activities, work in dry, hot or polluted locations, and positions that cause mental or physical fatigue leading to burnout have been associated with the use of alcohol as relief for tension and suffering. (3)(4)(5)(6) Some researchers have investigated the sociodemographic factors associated with alcohol use among workers; (7,8) however, studies with the specific population of maintenance workers were not identified. Most prior studies on alcoholism among workers (1,4,(9)(10)(11)(12)(13) chiefly consider hazardous use or dependence symptoms without specifically analyzing factors such as frequency of consumption or binge drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os problemas e agravos à saúde mais frequentes, pode-se destacar sobrepeso e obesidade, diabetes, hipertensão, hipercolesterolemia, alterações posturais, privação e distúrbios do sono, sonolência excessiva e estresse (Ferreira & Alvarez, 2013;Leyton et al, 2012;Oliveira et al, 2015;Penteado, Gonçalves, Costa, & Marques, 2008;Pylkkönen et al, 2015;Ulhôa et al, Resumen 2010).O estudo de Cerqueira-Santos e Santana (2014), ao analisar a percepção da satisfação com o trabalho de 342 motoristas de caminhão, autônomos e empregados, de diversos estados do Brasil, demonstrou que os motoristas que tinham vínculo empregatício indicaram maior satisfação com a empresa quando comparados aos autônomos.…”
unclassified